1991
DOI: 10.1001/jama.1991.03470220070029
|View full text |Cite
|
Sign up to set email alerts
|

Does Tobacco Advertising Target Young People to Start Smoking?

Abstract: Perception of advertising is higher among young smokers; market-share patterns across age and sex groups follow the perceived advertising patterns; and changes in market share resulting from advertising occur mainly in younger smokers. Cigarette advertising encourages youth to smoke and should be banned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
5

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(37 citation statements)
references
References 16 publications
0
32
0
5
Order By: Relevance
“…En Estados Unidos de América, cerca del 64% de los escolares han experimentado con el tabaco, siendo la prevalencia de tabaquismo del orden del 10% al 15%. Ésta se incrementa con la edad [12][13][14] .…”
Section: Smoking During Early Adolescence a Study In Schoolchildren unclassified
“…En Estados Unidos de América, cerca del 64% de los escolares han experimentado con el tabaco, siendo la prevalencia de tabaquismo del orden del 10% al 15%. Ésta se incrementa con la edad [12][13][14] .…”
Section: Smoking During Early Adolescence a Study In Schoolchildren unclassified
“…[15][16][17][18][19] However the present study revealed that tobacco industry advertisement on billboard are not associated with tobacco use among adolescents. This inconsistency might be due to there is a ban of advertisement of tobacco products and sponsorships by tobacco industries on media, billboard, and any sport or other events.…”
mentioning
confidence: 71%
“…After the third exposure advertisers should focus on reach rather than frequency, according to research findings from advertising effects research (Vakratsas and Ambler 1999). A study of the connection between the brand that new (teenage) smokers select, and the advertising for cigarette brands found a correlation of 0.93 between advertising amount and brand selection (Pierce, Gilpin et al 1991;Pucci and Siegel 1999). Biel found that reducing advertising during a recession does not pay.…”
Section: Behavioral Effects Of Advertising or Commercial Campaignsmentioning
confidence: 99%